Penerapan Framework ITIL V4 Pada Evaluasi Tata Kelola Insiden dan Masalah Layanan It di PT. Putra Laskar Merdeka - Matthew Vincentius Triwahono; Mulyati Mulyati (Jurnal Sosial Teknologi, 2026)
This study examines the implementation of the ITIL V4 framework in incident and problem management of IT services at PT Putra Laskar Merdeka (PLM), focusing on analyzing the effectiveness of IT operations supporting solar distribution. ITIL V4 was used to evaluate the reactive incident management practices and the poorly documented problem management processes. The results show a significant gap between the current state and ITIL V4 best practices, indicating that PT PLM needs to adopt a more structured approach, such as a centralized ticketing system, to improve service recovery effectiveness and prevent recurring incidents. Additionally, transforming from a reactive to a proactive approach in incident and problem management can enhance end-user satisfaction and support business continuity. The study offers strategic and technical recommendations, including the implementation of standardized procedures and improvements in IT asset management.